Factors Influencing Eating Behaviors Among Teenage Pregnant Women - ลีลาทิวานนท์ ธารินันท์; ชูนวล โสเพ็ญ; ยังวนิชเศรษฐ สุนันทา (Princess of Naradhiwas University Journal, 2018)
This predictive research aimed to study the level of eating behaviors and factors influencing eating behaviors among teenage pregnant women. The sample consisted of 200 teenage pregnant women who visited antenatal clinics at Hatyai Hospital and Songkla Hospital. The research instruments for data collection comprised 7 questionnaires. The content validity of all questionnaires was judged by 3 experts. The reliability of questionnaires 2-6 were tested using Cronbach’s alpha coefficient, yielding values of 0.80, 0.88, 0.85, 0.86 and 0.89 respectively. The reliability of questionnaire 7 was tested using Kuder-Richardson (KR-20) yielding a value of 0.77. Data were analyzed using percentage, mean, and standard deviation. The predictability was analyzed using multiple regression. The result showed that eating behavior of teenage pregnant women was at a good level (M = 65.71, S.D. = 6.58). Regression modeling showed that self-efficacy of eating behavior, social support of eating behavior, and belief of eating behavior could explain 37 percent of the variation. (R2 = .37, p < .001). The results of this study could be used as basic information to promote optimal eating behavior among teenage pregnant woman.